Prevalencia odontológica de caries dental, en escolares de 6 a 12 años, pertenecientes al cantón Huaquillas - provincia del Oro, Ecuador, 2018 - 2019 - Luzón Caigua, Karen Lizbeth (2022)
Dental caries is a multifactorial disease caused by the conversion of free sugars to fermentable acids, combined with insufficient exposure to fluoride and poor oral hygiene, resulting in the appearance of carious lesions; in Ecuador, it represents a public health problem where we have reported high rates. The objective of this research work was to determine the prevalence of dental caries according to the classification by the International Classification Code of Diseases, tenth edition, concerning age and sex, as well as the comparison of this prevalence in the years 2018-2019 in schoolchildren aged 6 to 12 years, belonging to the canton Huaquillas - Province of El Oro, Ecuador the present study was a descriptive-transversal, epidemiological and retrospective design. Furthermore, the results of this study revealed a prevalence of 39.71% of dental caries. In addition, a slight predilection for the female sex with 53.06% of the diagnosed cases, and the most prevalent type of caries; according to the International Classification Code of Diseases tenth edition, was dentin caries with 87.57%, we also evidenced that from 2018 to 2019 the cases of dental care for carious lesions increased significantly, on the other hand, despite this increase, the prevalence decreased to 31.11%. Finally, we conclude from these data that dental caries continue to be a public health problem with a high demand for dental care; likewise, a reduction in prevalence can be seen, which indicates a positive response from the population to this condition